An e-government framework for assessing readiness for public sector e-procurement in a lower-middle income country. Issue 4 (1st October 2020) - Adjei-Bamfo, Peter; Domfeh, Kwame Ameyaw; Bawole, Justice Nyigmah; Ahenkan, Albert; Maloreh-Nyamekye, Theophilus; Adjei-Bamfo, Stephanie; Darkwah, Samuel Antwi
ABSTRACT: Governments globally are leveraging information and communication technology (ICT) growth towards improving the quality of public procurement services for socio-economic development. However, the extent of its application differs across nations. Notwithstanding the extant theoretical and empirical literature on IT for development, knowledge on how to assess readiness for adopting a full e-procurement system in the public sector of lower and lower-middle income countries (LMICs) begs for understanding. With the narrative of Ghana, we address this gap by drawing on the institutional and economic theory and the United Nations E-Government Development Index towards a holistic framework beyond the dyad of linear website functionalities and internet focus of prior e-government adoption models. Elite interviews gathered from multiple cases from Ghana's public sector reveals the key readiness determinants for a full public sector e-procurement system. This study has significant implications for shaping the process-oriented management of government e-procurement projects towards socio-economic development in LMICs amid their complex institutional and socio-technical environments.